Case report: Neonatal diabetes mellitus caused by KCNJ11 mutation presenting with intracranial hemorrhage - Wu, Bo; Xu, Wei (Frontiers in Neurology, 2023)
Neonatal diabetes mellitus (NDM) is a rare type of monogenic diabetes. At present, most published studies have focused on the types of gene mutations associated with NDM and the therapeutic effect of sulfonylureas (SUs) on the disease; few studies on NDM-associated intracranial hemorrhage (ICH) exist. In addition, p.V59M mutations generally lead to intermediate DEND (iDEND: intermediate developmental delay and neonatal diabetes) syndrome without epilepsy. Here, we present a case of a 1-month-old male infant who was diagnosed with NDM caused by a KCNJ11 missense mutation (p.V59M), presenting with cerebral injury. In the early stage of the disease, continuous insulin dose adjustment did not achieve an ideal level of blood glucose. Although blood glucose was subsequently controlled by oral SUs, which were administered after the genetic test result, the patient still displayed epilepsy and developmental delay. In this case report, we present our experience in the treatment of the infant, switching from insulin to oral SUs and we thought that SUs have limited effects on improving the prognosis of neurodevelopmental disturbances in NDM with foci of encephalomalacia. In addition, there may be a relationship between KCNJ11 missense mutations and cerebral injury, and further research must be carried out to confirm these points.